2014
DOI: 10.1186/1471-2458-14-1180
|View full text |Cite
|
Sign up to set email alerts
|

Gender variations in access, choice to use and cleaning of shared latrines; experiences from Kampala Slums, Uganda

Abstract: BackgroundSanitation is one of the most intimate issues that affect women, especially in slums of developing countries. There are few studies that have paid attention to the gender variations in access, choice to use and cleaning of shared latrines in slums.MethodsThis paper draws on qualitative data from a cross sectional study conducted between 2012 and 2013 in six slums of Kampala City, Uganda. The study involved both women and men. Data were collected from 12 Focus Group Discussions (FGDs), 15 Key informan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 31 publications
3
66
0
2
Order By: Relevance
“…The minimal disposal of other wastes in pit latrines could be due to the users being conscious of high filling rates of their latrines. Further, while disposal of sanitary wastes like baby diapers and menstrual pads in pit latrines was mentioned, earlier studies have shown that menstrual hygiene in slum is mainly by re-usable material owing to the expenses involved in buying pads (Kwiringira, Atekyereza, Niwagaba, & Günther, 2014b). Therefore, other factors rather than external waste streams account for the poor performance of pit latrines in the studied slums.…”
Section: Status Of Pit Latrine Structuresmentioning
confidence: 87%
“…The minimal disposal of other wastes in pit latrines could be due to the users being conscious of high filling rates of their latrines. Further, while disposal of sanitary wastes like baby diapers and menstrual pads in pit latrines was mentioned, earlier studies have shown that menstrual hygiene in slum is mainly by re-usable material owing to the expenses involved in buying pads (Kwiringira, Atekyereza, Niwagaba, & Günther, 2014b). Therefore, other factors rather than external waste streams account for the poor performance of pit latrines in the studied slums.…”
Section: Status Of Pit Latrine Structuresmentioning
confidence: 87%
“…For example, a school-based latrine cleanliness intervention did not increase latrine use among pupils (an outcome not included in other latrine cleanliness studies), despite an increase in cleaner latrines. 55 On the other hand, several latrine cleanliness interventions have shown evidence of cleaner latrines, [56][57][58][59] and latrine coverage interventions cite cleaner latrines as being used more often. 32 Cleaning behavior, like latrine use, is complex and influenced by a host of factors, such as, psychosocial factors, 60 commitment to cleaning, 57 seasonality, 59 and the physical structure of the latrine.…”
Section: Discussionmentioning
confidence: 99%
“…56 Most often, women are regulated to cleaning tasks. 58 Thus, cleaning programs that target community power structures may play a role in ultimately changing latrine use behavior as well. Unfortunately, there are few examples of this in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they volunteered to clean sanitation facilities because they had young children who would be exposed to the risk of disease. Women have often been responsible for sanitation, including cleaning, also reported among users of shared facilities in Uganda [65] and India [60]. However, when users depend on actions of specific individuals and do not put in their own effort, it is possible that such beneficial actions of specific individuals may stop when circumstances change e.g.…”
Section: Discussionmentioning
confidence: 99%